The idiopathic normal‐pressure hydrocephalus Radscale: a radiological scale for structured evaluation. (2nd February 2018) - Kockum, K.; Lilja‐Lund, O.; Larsson, E.‐M.; Rosell, M.; Söderström, L.; Virhammar, J.; Laurell, K.
Abstract : Background and purpose: Despite the important role of imaging in diagnosing idiopathic normal‐pressure hydrocephalus (iNPH), a structured overall assessment of radiological signs is still lacking. The purpose of this study was to construct a radiological scale, composed of morphological signs of iNPH, and compare it with clinical symptoms. Methods: In this prospective, population‐based study of iNPH, 168 individuals (93 females) [mean age 75 (range 66–92) years] underwent computed tomography of the brain and a neurological examination with assessment of clinical symptoms according to Hellström's iNPH scale. Two radiologists, blinded to clinical data, independently evaluated and measured eight radiological parameters, i.e. Evans' index, callosal angle, size of temporal horns, narrow high‐convexity sulci, dilated Sylvian fissures, focally dilated sulci, peri‐ventricular hypodensities and bulging of the lateral ventricular roof. Results: In a linear regression model, all parameters except ventricular roof bulging were significantly associated with clinical iNPH symptoms. The seven remaining parameters were summarized into a total iNPH Radscale score ranging from 0 to 12. There was a significant correlation ( r  = 0.55, P  <   0.001) between the total iNPH Radscale score and clinical symptoms. The inter‐rater agreement for the included radiological parameters was high (intraclass correlation, 0.74–0.97). Conclusion: The iNPH Radscale may become a valuable diagnostic screening tool, allowing a structured radiological assessment. A high iNPH Radscale score together with clinical symptoms should raise suspicion of iNPH, motivating further evaluation for shunt surgery.